The square root of a product

When we encounter a root that encompasses the entirety of the product, we can decompose the factors of the products and leave a separate root for each of them. Let's not forget to leave the multiplication sign between the factors we have extracted.

Let's put it this way:
(ab)=ab\sqrt{(a\cdot b)}=\sqrt{a}\cdot\sqrt{b}

Practice Product Property of Square Roots

Examples with solutions for Product Property of Square Roots

Exercise #1

Solve the following exercise:

161= \sqrt{16}\cdot\sqrt{1}=

Video Solution

Step-by-Step Solution

Let's start by recalling how to define a root as a power:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

Next, we will remember that raising 1 to any power will always yield the result 1, even the half power of the square root.

In other words:

161=1612=16112=161=16=4 \sqrt{16}\cdot\sqrt{1}= \\ \downarrow\\ \sqrt{16}\cdot\sqrt[2]{1}=\\ \sqrt{16}\cdot 1^{\frac{1}{2}}=\\ \sqrt{16} \cdot1=\\ \sqrt{16} =\\ \boxed{4} Therefore, the correct answer is answer D.

Answer

4 4

Exercise #2

Solve the following exercise:

12= \sqrt{1}\cdot\sqrt{2}=

Video Solution

Step-by-Step Solution

Let's start by recalling how to define a square root as a power:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

Next, we remember that raising 1 to any power always gives us 1, even the half power we got from converting the square root.

In other words:

12=122=1122=12=2 \sqrt{1} \cdot \sqrt{2}= \\ \downarrow\\ \sqrt[2]{1}\cdot \sqrt{2}=\\ 1^{\frac{1}{2}} \cdot\sqrt{2} =\\ 1\cdot\sqrt{2}=\\ \boxed{\sqrt{2}} Therefore, the correct answer is answer a.

Answer

2 \sqrt{2}

Exercise #3

Solve the following exercise:

301= \sqrt{30}\cdot\sqrt{1}=

Video Solution

Step-by-Step Solution

Let's start with a reminder of the definition of a root as a power:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

We will then use the fact that raising the number 1 to any power always yields the result 1, particularly raising it to the power of half of the square root (which we obtain by using the definition of a root as a power mentioned earlier).

In other words:

301=3012=30112=301=30 \sqrt{30}\cdot\sqrt{1}= \\ \downarrow\\ \sqrt{30}\cdot\sqrt[2]{1}=\\ \sqrt{30}\cdot 1^{\frac{1}{2}}=\\ \sqrt{30} \cdot1=\\ \boxed{\sqrt{30}}

Therefore, the correct answer is answer C.

Answer

30 \sqrt{30}

Exercise #4

Solve the following exercise:

25x4= \sqrt{25x^4}=

Video Solution

Step-by-Step Solution

To simplify the given expression, we will use the following three laws of exponents:

a. Definition of root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

b. Law of exponents for an exponent applied to terms in parentheses:

(ab)n=anbn (a\cdot b)^n=a^n\cdot b^n

c. Law of exponents for an exponent raised to an exponent:

(am)n=amn (a^m)^n=a^{m\cdot n}

We'll start by converting the fourth root to an exponent using the law of exponents mentioned in a.:

25x4=(25x4)12= \sqrt{25x^4}= \\ \downarrow\\ (25x^4)^{\frac{1}{2}}=

We'll continue, using the law of exponents mentioned in b. and apply the exponent to each factor in the parentheses:

(25x4)12=2512(x4)12 (25x^4)^{\frac{1}{2}}= \\ 25^{\frac{1}{2}}\cdot(x^4)^{{\frac{1}{2}}}

We'll continue, using the law of exponents mentioned in c. and perform the exponent applied to the term with an exponent in parentheses (the second factor in the multiplication):

2512(x4)12=2512x412=2512x2=25x2=5x2 25^{\frac{1}{2}}\cdot(x^4)^{{\frac{1}{2}}} = \\ 25^{\frac{1}{2}}\cdot x^{4\cdot\frac{1}{2}}=\\ 25^{\frac{1}{2}}\cdot x^{2}=\\ \sqrt{25}\cdot x^2=\\ \boxed{5x^2}

In the final steps, we first converted the power of one-half applied to the first factor in the multiplication back to the fourth root form, again, according to the definition of root as an exponent mentioned in a. (in the reverse direction) and then calculated the known fourth root of 25.

Therefore, the correct answer is answer a.

Answer

5x2 5x^2

Exercise #5

Solve the following exercise:

25= \sqrt{2}\cdot\sqrt{5}=

Video Solution

Step-by-Step Solution

In order to simplify the given expression we use two laws of exponents:

A. Defining the root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}} B. The law of exponents for dividing powers with the same bases (in the opposite direction):

xnyn=(xy)n x^n\cdot y^n =(x\cdot y)^n

Let's start by changing the square roots to exponents using the law of exponents shown in A:

25=212512= \sqrt{2}\cdot\sqrt{5}= \\ \downarrow\\ 2^{\frac{1}{2}}\cdot5^{\frac{1}{2}}= We continue: since we are multiplying two terms with equal exponents we can use the law of exponents shown in B and combine them together as the same base raised to the same power:

212512=(25)12=1012=10 2^{\frac{1}{2}}\cdot5^{\frac{1}{2}}= \\ (2\cdot5)^{\frac{1}{2}}=\\ 10^{\frac{1}{2}}=\\ \boxed{\sqrt{10}} In the last steps wemultiplied the bases and then used the definition of the root as an exponent shown earlier in A (in the opposite direction) to return to the root notation.

Therefore, the correct answer is answer B.

Answer

10 \sqrt{10}

Exercise #6

Solve the following exercise:

x4= \sqrt{x^4}=

Video Solution

Step-by-Step Solution

In order to simplify the given expression, we will use the following three laws of exponents:

a. The definition of root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

b. Law of exponents for power to a power:

(am)n=amn (a^m)^n=a^{m\cdot n}

Let's start with converting the square root to an exponent using the law of exponents mentioned in a:

x4=(x4)12= \sqrt{x^4}= \\ \downarrow\\ (x^4)^{\frac{1}{2}}= Let's continue, using the law of exponents mentioned in b to perform the exponentiation of the term in parentheses:

(x4)12=x412=x2 (x^4)^{{\frac{1}{2}}} = \\ x^{4\cdot\frac{1}{2}}=\\ \boxed{x^2} Therefore, the correct answer is answer b.

Answer

x2 x^2

Exercise #7

Solve the following exercise:

36x= \sqrt{36x}=

Video Solution

Step-by-Step Solution

In order to simplify the given expression, we will use the following two laws of exponents:

a. The definition of root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

b. The law of exponents for an exponent applied to terms in parentheses:

(ab)n=anbn (a\cdot b)^n=a^n\cdot b^n

Let's start by converting the square root to an exponent using the law of exponents mentioned in a:

36x=(36x)12= \sqrt{36x}= \\ \downarrow\\ (36x)^{\frac{1}{2}}=

Next, we'll use the law of exponents mentioned in b and apply the exponent to each factor within the parentheses:

(36x)12=3612x12=36x=6x (36x)^{\frac{1}{2}}= \\ 36^{\frac{1}{2}}\cdot x^{{\frac{1}{2}}}=\\ \sqrt{36}\sqrt{x}=\\ \boxed{6\sqrt{x}}

In the final steps, we first converted the power of one-half applied to each factor in the multiplication back to square root form, again, according to the definition of root as an exponent mentioned in a (in the opposite direction) and then calculated the known square root of 36.

Therefore, the correct answer is answer c.

Answer

6x 6\sqrt{x}

Exercise #8

Solve the following exercise:

33= \sqrt{3}\cdot\sqrt{3}=

Video Solution

Step-by-Step Solution

In order to simplify the given expression, we will use two laws of exponents:

a. The definition of a root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}} b. The law of exponents for power of a power:

(am)n=amn (a^m)^n=a^{m\cdot n}

Let's start by converting the square roots to exponents using the law mentioned in a:

33=312312= \sqrt{3}\cdot\sqrt{3}= \\ \downarrow\\ 3^{\frac{1}{2}}\cdot3^{\frac{1}{2}}= Let's continue, notice that we got a number multiplied by itself, therefore, according to the definition of exponents we can write the expression we got as a power of that same number, then we'll use the law of exponents mentioned in b and perform the exponentiation of the term in parentheses:

312312=(312)2=3122=31=3 3^{\frac{1}{2}}\cdot3^{\frac{1}{2}}= \\ (3^{\frac{1}{2}})^2=\\ 3^{\frac{1}{2}\cdot2}=\\ 3^1=\\ \boxed{3} Additionally, we identify that:

3=9 3=\sqrt{9} Therefore, the correct answer (most accurate) is answer d.

Answer

Answers a + b

Exercise #9

Solve the following exercise:

1625= \sqrt{16}\cdot\sqrt{25}=

Video Solution

Step-by-Step Solution

In order to simplify the given expression, we will use two laws of exponents:

a. The definition of root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

b. The law of exponents for an exponent applied to a product in parentheses (in reverse direction):

xnyn=(xy)n x^n\cdot y^n =(x\cdot y)^n

Let's start by converting the square roots to exponents using the law of exponents mentioned in a':

1625=16122512= \sqrt{16}\cdot\sqrt{25}= \\ \downarrow\\ 16^{\frac{1}{2}}\cdot25^{\frac{1}{2}}=

We'll continue, since there is a multiplication between two terms with identical exponents, we can use the law of exponents mentioned in b' and combine them together in parentheses which are raised to the same exponent:

16122512=(1625)12=40012=400=20 16^{\frac{1}{2}}\cdot25^{\frac{1}{2}}= \\ (16\cdot25)^{\frac{1}{2}}=\\ 400^{\frac{1}{2}}=\\ \sqrt{400}=\\ \boxed{20}

In the final steps, we performed the multiplication within the parentheses and again used the definition of root as an exponent mentioned in a' (in reverse direction) to return to root notation.

Therefore, the correct answer is answer d.

Answer

20 20

Exercise #10

Solve the following exercise:

510= \sqrt{5}\cdot\sqrt{10}=

Video Solution

Step-by-Step Solution

In order to simplify the given expression, we will use two laws of exponents:

a. The definition of root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

b. The law of exponents for an exponent applied to terms in parentheses (in reverse direction):

xnyn=(xy)n x^n\cdot y^n =(x\cdot y)^n

Let's start by converting the square roots to exponents using the law of exponents mentioned in a':

510=5121012= \sqrt{5}\cdot\sqrt{10}= \\ \downarrow\\ 5^{\frac{1}{2}}\cdot10^{\frac{1}{2}}=

We'll continue, since there is multiplication between two terms with identical exponents, we can use the law of exponents mentioned in b' and combine them together in parentheses which are raised to the same exponent:

5121012=(510)12=5012=50 5^{\frac{1}{2}}\cdot10^{\frac{1}{2}}= \\ (5\cdot10)^{\frac{1}{2}}=\\ 50^{\frac{1}{2}}=\\ \boxed{\sqrt{50}}

In the final steps, we performed the multiplication within the parentheses and again used the definition of root as an exponent mentioned in a' (in reverse direction) to return to root notation.

Therefore, the correct answer is answer c.

Answer

50 \sqrt{50}

Exercise #11

Solve the following exercise:

23= \sqrt{2}\cdot\sqrt{3}=

Video Solution

Step-by-Step Solution

In order to simplify the given expression, we will use two laws of exponents:

a. The definition of root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

b. The law of exponents for exponents applied to terms in parentheses (in reverse):

xnyn=(xy)n x^n\cdot y^n =(x\cdot y)^n

Let's start by converting the square roots to exponents using the law of exponents mentioned in a':

23=212312= \sqrt{2}\cdot\sqrt{3}= \\ \downarrow\\ 2^{\frac{1}{2}}\cdot3^{\frac{1}{2}}=

We'll continue, since there is multiplication between two terms with identical exponents, we can use the law of exponents mentioned in b' and combine them together in parentheses which are raised to the same exponent:

212312=(23)12=612=6 2^{\frac{1}{2}}\cdot3^{\frac{1}{2}}= \\ (2\cdot3)^{\frac{1}{2}}=\\ 6^{\frac{1}{2}}=\\ \boxed{\sqrt{6}}

In the final steps, we performed the multiplication within the parentheses and again used the definition of root as an exponent mentioned earlier in a' (in reverse) to return to root notation.

Therefore, the correct answer is answer b.

Answer

6 \sqrt{6}

Exercise #12

Solve the following exercise:

56= \sqrt{5}\cdot\sqrt{6}=

Video Solution

Step-by-Step Solution

In order to simplify the given expression, we will use two laws of exponents:

a. The definition of root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}}

b. The law of exponents for exponents applied to terms in parentheses (in reverse):

xnyn=(xy)n x^n\cdot y^n =(x\cdot y)^n

We'll start by converting the square roots to exponents using the law of exponents mentioned in a':

56=512612= \sqrt{5}\cdot\sqrt{6}= \\ \downarrow\\ 5^{\frac{1}{2}}\cdot6^{\frac{1}{2}}=

We'll continue, since there is multiplication between two terms with identical exponents, we can use the law of exponents mentioned in b' and combine them together in parentheses raised to the same exponent:

512612=(56)12=3012=30 5^{\frac{1}{2}}\cdot6^{\frac{1}{2}}= \\ (5\cdot6)^{\frac{1}{2}}=\\ 30^{\frac{1}{2}}=\\ \boxed{\sqrt{30}}

In the final steps, we performed the multiplication within the parentheses and again used the definition of root as an exponent mentioned in a' (in reverse) to return to root notation.

Therefore, the correct answer is answer d.

Answer

30 \sqrt{30}

Exercise #13

Solve the following exercise:

55= \sqrt{5}\cdot\sqrt{5}=

Video Solution

Step-by-Step Solution

In order to simplify the given expression, we will use two laws of exponents:

a. The definition of root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}} b. The law of exponents for multiplication between terms with identical bases:

aman=am+n a^m\cdot a^n=a^{m+n}

Let's start by converting the square roots to exponents using the law mentioned in a:

55=512512= \sqrt{5}\cdot\sqrt{5}= \\ \downarrow\\ 5^{\frac{1}{2}}\cdot5^{\frac{1}{2}}= We'll continue, since we are multiplying two terms with identical bases - we'll use the law of exponents mentioned in b:

512512=512+12=51=5 5^{\frac{1}{2}}\cdot5^{\frac{1}{2}}= \\ 5^{\frac{1}{2}+\frac{1}{2}}=\\ 5^1=\\ \boxed{5} Therefore, the correct answer is answer a.

Answer

5 5

Exercise #14

Solve the following exercise:

77= \sqrt{7}\cdot\sqrt{7}=

Video Solution

Step-by-Step Solution

In order to simplify the given expression, we will use two laws of exponents:

a. The definition of root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}} b. The law of exponents for multiplication between terms with identical bases:

aman=am+n a^m\cdot a^n=a^{m+n}

Let's start by converting the square roots to exponents using the law mentioned in a:

77=712712= \sqrt{7}\cdot\sqrt{7}= \\ \downarrow\\ 7^{\frac{1}{2}}\cdot7^{\frac{1}{2}}= We'll continue, since we are multiplying two terms with identical bases - we'll use the law of exponents mentioned in b:

712712=712+12=71=7 7^{\frac{1}{2}}\cdot7^{\frac{1}{2}}= \\ 7^{\frac{1}{2}+\frac{1}{2}}=\\ 7^1=\\ \boxed{7} Therefore, the correct answer is answer a.

Answer

7 7

Exercise #15

Solve the following exercise:

44= \sqrt{4}\cdot\sqrt{4}=

Video Solution

Step-by-Step Solution

In order to simplify the given expression, we will use two laws of exponents:

a. The definition of root as an exponent:

an=a1n \sqrt[n]{a}=a^{\frac{1}{n}} b. The law of exponents for power of a power:

(am)n=amn (a^m)^n=a^{m\cdot n}

Let's start by converting the square roots to exponents using the law mentioned in a':

44=412412= \sqrt{4}\cdot\sqrt{4}= \\ \downarrow\\ 4^{\frac{1}{2}}\cdot4^{\frac{1}{2}}= Let's continue, notice that we got a number multiplied by itself, therefore, according to the definition of exponents we can write the expression we got as a power of that same number, then - we'll use the law of exponents mentioned in b' and perform the exponent operation on the term in parentheses:

412412=(412)2=4122=41=4 4^{\frac{1}{2}}\cdot4^{\frac{1}{2}}= \\ (4^{\frac{1}{2}})^2=\\ 4^{\frac{1}{2}\cdot2}=\\ 4^1=\\ \boxed{4} Therefore, the correct answer is answer c.

Answer

4 4